The Notable of Lablab Seed as a Feed Supplement for Goat Fed Roughages Diet - Ismartoyo (Research Advances and Challenges in Agricultural Sciences Vol. 2, 2024)
An experiment was conducted to examine nutrients intake and digestibility of low-quality roughages supplemented with Lablab purpureus seed fed to goat. Total of 25 goats were kept in an individual metabolism crate and fed 5 diets containing roughage ad libitum and supplements of Lablab purpureus (var. Highworth) seed or sweet lupin seed (Lupinus angustifolius). The 5 diets offered were: TI=roughage alone, T2=roughage+0.3% LW Lablab seed, T3=roughage+0.6% LW Lablab seed, T4=roughage+1.2% LW Lablab seed, and T5=roughage+1.2% LW Lupin seed. Results of this experiment showed that roughage intake was not significantly difference (p>0.05) between 0.3% or 0.6% LW levels of Lablab of by 1.2% LW lupin supplementation, but was reduced (p<0.05) by 35% by 1.2% LW Lablab supplement. Organic matter (OM) digestibility was increased by all supplements, and digestible OM intake was increased by the 0.6% LW Lablab and 1.2% LW lupin supplements. LW gain and feed conversion ratio were not changed (p>0.05) by 0.3% or 0.6% LW Lablab or the 1.2% LW lupin, but were reduced (p<0.05) by the 1.2% LW Lablab supplement. It was concluded that goats could efficiently utilize supplements of Lablab purpureus seed fed at levels of up to 0.6% LW. However, when 1.2% LW of the Lablab seed was fed, poor performance suggested that the goats might be adversely affected by anti-nutritional factors content in the seed of Lablab.